Dislocation-Controlled Low-Temperature Superplastic Deformation of Ti-6Al-4V Alloy - Liu, Chao; Wang, Xin; Zhou, Ge; Li, Feng; Zhang, Siqian; Zhang, Haoyu; Chen, Lijia; Liu, Haijian (Frontiers in Materials, 2021)
The superplastic elongation and deformation mechanism of Ti-6Al-4V alloy at 923 K and elongation speed of 10-3, 5×10-3 or 5×10-2 s-1 were studied on an AG 250KNE electronic elongation tester. Through theoretical modeling, the unit dislocation count of this alloy during superplastic deformation was introduced into the Ruano-Wadsworth-Sherby (R-W-S) deformation mechanism map, and a new deformation mechanism map involving dislocation count was plotted. Thereby, the mechanism underling the low-temperature superplastic deformation of this alloy was predicted. It was found the superplastic elongation of Ti-6Al-4V at the tested temperature was controlled by dislocation movement, and with the accelerated elongation speed, the deformation transited from the dislocation-controlled mechanism with a stress index of 4 to the dislocation glide mechanism with a stress index of 5 or 7. At the strain rate of 10-3 s-1, this alloy acquired the largest elongation rate of 790% and strain rate sensitivity index of 0.52 and had excellent low-temperature superplastic properties.